BASRA Ulama and Medina Porch of Madura; Portrait of religious freedom in Madura - Mukhlishi & Surya Fajar Rasyid (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
The idea of BASRA piousman about religion freedom in Madura is becomes very urgent to be raised to the surface, the idea of the issue of religious freedom which is became the ideals of BASRA in Madura is factual to be transformed amid the discourse to make Madura as the Serambi Medinah. Madura piousman Council BASRA tries to transform Islamic teachings primarily in relation to freedom from normative to praxis. For this purpose, the varied model of understanding, ranging from the cultural understanding with the general public, the selective structural and criticize and examine government policies that can erode Indonesia culture generally and Madura in particularly. In the globalization era is a lot of attacking each other by using SARA, whereas NKRI is final which means to be forward-thinking who have agreed we live in diversity that also once practiced the prophet in the Medina charter that is able to serve the minorities such as Jews and Christians.